Deteksi resistensi insektisida sintetik piretroid pada Aedes aegypti (l.) Strain palembang menggunakan teknik polymerase chain reaction - Ahmad Giffari; Humairo Fatimi; Chairil Anwar (ASPIRATOR - Journal of Vector-borne Disease Studies, 2013)
Aedes aegypti is a vector of several pathogens including dengue fever/dengue hemorrhagic fever virus. Five hundred thousand dengue haemorrhagic fever new cases occur every year throughout the world. Vector control is an effective way to break the transmission; unfortunately constant insecticide ultimately caused resistance. Insecticides resistance in Ae.aegypti was first discovered on trichloroetane diphenyl dichloro (DDT), followed by temephos and synthetic pyrethroid. Three detection ways according to WHO procedure are bioassay, biochemistry and molecular. The biochemical detection that conducted previously in Palembang were turned out negative, nevertheless incidence rate has not yet decreased. Molecular detection is needed to determine the mechanisms of insecticide resistance. Molecular detection can detect gene mutations in the metabolic enzyme and target site insecticides, such as the voltage gated sodium channel (VGSC). The purpose of research was to identify the Val1016Ile and Val1016Gly point mutation in the VGSC gene of Ae.aegypti in Palembang. Population were all 3rd and 4th instar larvae of Ae.aegypti derived from breeding eggs obtained from villages of Bukit Kecil, Ilir timur I and Sukarami sub distric. Identification took place in BBLK Palembang while molecular test took place both in BBLK Palembang and Clinical Microbiology Department of Muhammad Hoesin Hospital Palembang. Results showed that there has been Val1016Ile point mutation and there is no Val1016Gly point mutation of voltage gated sodium channel gene. It can be concluded that there has been Val1016Ile point mutation in the voltage gated sodium channel gene of Ae.aegypti as the marker of synthetic pyrethroid insecticides resistance in Palembang